2019
DOI: 10.1111/gcbb.12623
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of small organic acids present in fast pyrolysis bio‐oil from lignocellulose as feedstocks for bacterial bioconversion

Abstract: Small organic acids derived from fast pyrolysis of lignocellulosic biomass represent a significant proportion of microbially accessible carbon in bio‐oil. However, using bio‐oil for microbial cultivation is a highly challenging task due to its strong adverse effects on microbial growth as well as its complex composition. In this study, the main small organic acids present in bio‐oil as acetate, formate and propionate were evaluated with respect to their suitability as feedstocks for bacterial growth. For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…A multitude of procedures have already been described for the elimination of potential inhibitors from aqueous pyrolysis products and hydrolysates. Among them, the most common ones are extractions [ 11 , 21 ], adsorption processes using activated carbon [ 22 25 ] or other adsorbents [ 26 ], ion exchange [ 27 ] as well as overliming [ 28 30 ] and rotary evaporation [ 10 ]. In addition to these physical and chemical methods, biological treatments using whole cells [ 31 , 32 ] or enzymes [ 33 ] can also be applied to reduce the toxicity of liquid pyrolysis products.…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of procedures have already been described for the elimination of potential inhibitors from aqueous pyrolysis products and hydrolysates. Among them, the most common ones are extractions [ 11 , 21 ], adsorption processes using activated carbon [ 22 25 ] or other adsorbents [ 26 ], ion exchange [ 27 ] as well as overliming [ 28 30 ] and rotary evaporation [ 10 ]. In addition to these physical and chemical methods, biological treatments using whole cells [ 31 , 32 ] or enzymes [ 33 ] can also be applied to reduce the toxicity of liquid pyrolysis products.…”
Section: Introductionmentioning
confidence: 99%
“…Acetic acid had no negative influence on the growth of the two P. putida KT2440 strains (Figure b) until the highest applied acid concentration of 10 g/L. Furthermore, the strains metabolized acetic acid and partially used it for growth (Arnold, Tews, Tews, Kiefer, Henkel, & Hausmann, ). In detail, compared to cultivation without acetic acid (maximum OD 600 = 12.4), the wild type reached a maximum OD 600 of 14.6 and 15.1 at acetic acid concentrations of 2.5 and 10 g/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, benzoate metabolism is regulated by downstream metabolites in both Pseudomonas and Thauera (Boll and Fuchs, 1995; Schühle et al ., 2003; Sudarsan et al ., 2016). Most relevant, acetate is not an optimal growth substrate for Pseudomonads (Hintermayer and Weuster‐Botz, 2017; Arnold et al ., 2019). It has been formerly shown that growth of P .…”
Section: Discussionmentioning
confidence: 99%
“…It has been formerly shown that growth of P . putida is inhibited by high acetate concentrations; documented mechanisms include interference with amino acid biosynthesis, and alterations of ion and osmotic balance (Fieschko and Humphrey, 1985; Roe et al ., 1998; Roe et al ., 2002; Arnold et al ., 2019). This could explain the relatively high number of inactive cells observed in the assay of P .…”
Section: Discussionmentioning
confidence: 99%